2016
DOI: 10.1007/s11661-016-3429-3
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Hot Isostatic Pressing for Closing Porosity in Titanium Parts Manufactured by Selective Electron Beam Melting

Abstract: Ti-6Al-4V parts, produced by selective electron beam melting additive manufacturing, have been studied by X-ray computed tomography (XCT) to track pore closure during a standard hot isostatic pressing (HIPing) cycle. Comparison of repeated XCT scans before and after HIPing, on worst-case samples with different geometries, confirmed that all internal porosity was shrunk to below the resolution limit of the equipment used (~5 µm) following the HIPing cycle, apart from defects with surface connected ligaments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
92
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 223 publications
(98 citation statements)
references
References 18 publications
4
92
1
1
Order By: Relevance
“…To solve this problem, many aerospace companies are considering applying post-build hot isostatic pressing (HIPing) treatments to AM components. It has been reported that HIPIng of AM parts is very effective at closing porosity, which reduces internal stress concentrations, with a consequent increase in fatigue life [2,6].…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…To solve this problem, many aerospace companies are considering applying post-build hot isostatic pressing (HIPing) treatments to AM components. It has been reported that HIPIng of AM parts is very effective at closing porosity, which reduces internal stress concentrations, with a consequent increase in fatigue life [2,6].…”
mentioning
confidence: 99%
“…1b) to below the detection limit of the equipment used (~5 μm) [6]. Here, we aim to examine the effect of applying a typical β-anneal heat treatment on the porosity closed by HIPing.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…X-ray computed micro-tomography (CT) is one of the few techniques able to identify internal features within solid materials over a wide range of compositions. For AM, it has become an important 3D complement to 2D cross-sectional metallography in identifying pore volumes much lower than the particle feedstock [11].…”
Section: Introductionmentioning
confidence: 99%